The scope of employer's liability for negligence caused by 'Locum' medical practitioners - Jahn Kassim, Puteri Nemie; Abd. Manaf, Noor Hazilah (2015)
A locum is a person who temporarily fulfils the duties of another. ‘Locum’ medical practitioners (locums) are usually employed to relieve the regular and permanent medical practitioner who may be on leave or when the particular healthcare providers are short of staff. Many GP (General Practitioner) clinics opening for long hours deputize services to locums, who usually have a permanent employment elsewhere but are employed temporarily at these clinics to offer their clinical services. Most of the time, locums are appointed by these GP clinics without thinking of the legal consequences of the appointment. In particular, when things go wrong either with a patient or with the practice, it is very important to establish whether the ‘locum’ is an employee or an independent contractor. For the patient, their interests would be very much protected if the locum is classified as ‘an employee’ of the GP clinic. This is because the GP clinic as an employer would be liable for the acts and conducts of their employees including the locums. On the other hand, the GP clinic would prefer to categorise locums as independent contractors so that they will not be liable for any legal consequences that may arise from any negligent acts. This would be seen as going against the notion of fairness and justice as the fact that the GP clinics have economically benefited from the acts of the locums, it is proper that they should undertake the burden when things go wrong. Further, as an organization, the GP clinics can easily distribute the losses they had suffered. Thus, there is a need for clear policies and guidelines on the legal position of locums working in GP clinics considering the host of legal repercussions that may ensue.